2020
DOI: 10.1111/maps.13608
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigations of high‐pressure polymorphs in shocked ordinary chondrites

Abstract: Shock-induced melting textures and high-pressure polymorphs in 178 ordinary chondrites of all chemical groups and petrologic types were investigated. The shock-induced melting modes were classified into three types, namely pocket, line, and network. The type of shock-induced melting depends on the petrologic type. The width of the shock-induced melt increased with increasing the petrologic type number. The approximate estimated shock-pressure ranges recorded in and around the shock-induced melts of the H-group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 115 publications
(147 reference statements)
0
25
0
Order By: Relevance
“…In ordinary chondrites, wadsleyite and ringwoodite aggregates have been typically found within and/or in the surrounding of the shock features (Chen et al 2004;Yin et al 2018;Miyahara et al 2020), and ringwoodite has been also found in association with ferropericlase (Chen et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In ordinary chondrites, wadsleyite and ringwoodite aggregates have been typically found within and/or in the surrounding of the shock features (Chen et al 2004;Yin et al 2018;Miyahara et al 2020), and ringwoodite has been also found in association with ferropericlase (Chen et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Typical whole-area BSE images of investigated H/L/LL3 ordinary chondrites are shown in Figure S10. The modes of melting are shown in Tables S2-S4 and the definition of melting followed Miyahara et al (2020), that is, pocket, line, and network. The textures and constituents of shock-induced melts were similar to those of shocked ALH-78084 H3 and Y-793375 L3 chondrites (Figures 5a and 5b).…”
Section: Petrologic Type 3 Ordinary Chondritesmentioning
confidence: 99%
“…Miyahara et al. (2020) conducted systematic investigations of shock‐induced melts and high‐pressure minerals in ordinary chondrites and reported that some petrologic type 3 ordinary chondrites have shock‐induced melts and high‐pressure minerals such as coesite and Na‐pyroxene. Also, some petrologic type 3 ordinary chondrites with shock‐induced melts include flattened chondrules.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations